Use of intravenous immunoglobulins in clinical practice - E.K. Donyush ("Paediatrician" Publishers LLC, 2011)
Immunoglobulins are main component of immune defense; they take part in anti-infectious resistance of organism and regulate processes of different immune reactions. Intravenous immunoglobulins are the most frequently used products made from donor blood plasma. The need in these drugs is steadily increasing during last 15-20 years, and indications are widening due to modern hightechnology methods of production and cleaning. The article presents modern data on formula, mechanisms of action and indications for different groups of intravenous immunoglobulins (standard, hyperimmune, fortified) and description of possible adverse events.Key words: immuglobulines, prophylaxis, treatment, unfavorable reaction, children.